PEMAHAMAN UMAT KATOLIK DI STASI ST. YOSEF KARANGREJO, PAROKI REGINA PACIS MAGETAN TENTANG KEBANGKITAN BADAN DAN KEHIDUPAN KEKAL DALAM AJARAN GEREJA KATOLIK - Carolina Prolensia; Don Bosco Karnan Ardijanto (Bahasa Indonesia, 2019)
The death itself absolute and unavoidable, but it's also a definite and uncertain mystery. In front of death, the people helpless, but besides the people rebel because intheir soul there is seed of life that makes people reject and rebel against death. Based on this problem, so could be formulated some discussion: What do people interpret the death? What is the meaning of resurrection of the body? What does the meaning of resurrection of the body and eternal life? The purposes of this research are, describe the meaning of death, the meaning of body resurrection and eternal life, and how Catholic people at St. Joseph Karangrejo, Parish of Regina Pacis Magetan, understand about resurrection of the body and eternal life. This research uses qualitative research method. The Methods of data collection is done by direct interview in the field. Interviews are private between two parties. Conclusions of the research are that in common the catholics know the meaning of death. They know and believe that the resurrection and internal of the body and eternal life are real but they could not give a clear reason. They also know that there is relatoinship betwen daily life with internal life. Their daily life is preparation of their death and internal life. Their understanding is goad enough but still need to be strengthened and tobe cathecized.